Exploring the health care experiences of women diagnosed with vulvodynia. (12th January 2023) - Templeman, Lauren; Eberhardt, Judith; Ling, Jonathan
Abstract: Background: Although seeking diagnosis and treatment for chronic pain should be straightforward, this is not typically the case for those living with vulvodynia, who often describe it as a battle, frequently involving misdiagnosis, dismissal, and gender-based discrimination. Aim: This study explored the health care experiences of women living with vulvodynia in the United Kingdom. Methods: As they are less explored in literature, experiences postdiagnosis and across varying health care settings were specifically considered. Interviews were conducted with 6 women aged 21 to 30 years to explore their experiences when seeking help for vulvodynia. Outcomes: Through interpretative phenomenological analysis, 5 themes emerged: the impact of diagnosis, patients' perception of health care, self-guidance and lack of direction, gender as a barrier to effective care, and a lack of consideration of psychological factors. Results: Women often experienced difficulties before and after diagnosis, and many felt that their pain was dismissed and ignored due to their gender. Pain management was felt to be prioritized by health care professionals over well-being and mental health. Clinical Implications: There is a need for further exploration of gender-based discrimination experiences among patients with vulvodynia, health care professionals' perceptions of their capabilities in working with such patients, and the impact of improving professionals' training in working with these patients2 Strengths and Limitations: Health care experiences after diagnosis are rarely examined within literature, with studies predominantly focusing on experiences surrounding diagnosis, intimate relationships, and specific interventions. The present study provides an in-depth exploration of health care experiences through participants' lived experiences and gives insight into an underresearched area. Women with negative experiences of health care may have been more likely to participate than those with positive experiences, which may have resulted in their overrepresentation. Furthermore, participants were predominantly young White heterosexual women, and almost all had comorbidities, further limiting generalizability. Conclusion: Findings should be used to inform health care professionals' education and training to improve outcomes for those seeking care for vulvodynia.